2002
DOI: 10.1096/fj.02-0420fje
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic pulmonary artery fibroblasts trigger proliferation of vascular smooth muscle cells‐role of hypoxia‐inducible transcription factors

Abstract: Chronic lung hypoxia causes vascular remodeling with pulmonary artery smooth muscle cell (SMCPA) hyperplasia, resulting in pulmonary hypertension and cor pulmonale. We investigated SMCPA and pulmonary artery adventitial fibroblasts (FBPA) for their proliferative response to hypoxia. Strong SMCPA growth occurred under hypoxic conditions in SMCPA/FBPA co-cultures, but not in SMCPA monocultures. SMCPA growth was fully reproduced by transferring serum-free supernatant from hypoxic cultured FBPA to normoxic SMCPA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 26 publications
11
77
1
3
Order By: Relevance
“…High steady-state mRNA levels of HIF-3α were achieved in alveolar epithelial cells during sustained hypoxia. This finding supports earlier results which showed the abundantly expressed levels of HIF-3α mRNA in human pulmonary artery cells during hypoxia (1% O 2 , 24h) [39]. In previous studies, we demonstrated that HIF-1α mRNA and protein levels decreased in rat pulmonary artery cells during sustained hypoxia [40], thereby suggesting HIF-3α played an important role in lung responding to hypoxic damage.…”
Section: Discussionsupporting
confidence: 92%
“…High steady-state mRNA levels of HIF-3α were achieved in alveolar epithelial cells during sustained hypoxia. This finding supports earlier results which showed the abundantly expressed levels of HIF-3α mRNA in human pulmonary artery cells during hypoxia (1% O 2 , 24h) [39]. In previous studies, we demonstrated that HIF-1α mRNA and protein levels decreased in rat pulmonary artery cells during sustained hypoxia [40], thereby suggesting HIF-3α played an important role in lung responding to hypoxic damage.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, HIF-1a could be an important target for preventing metastasis. As such, suppression of HIF-1a, employing the techniques such as the transmission decoy technique (Rose et al, 2002), would be intriguing to suppress tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…While hypoxia-induced remodeling is associated with medial hypertrophy, direct stimulation of SMC proliferation by hypoxia remains somewhat controversial (37). Although there are reports of hypoxia driven smooth muscle cell proliferation (38,39), several in vitro studies have shown that hypoxia does not directly increase SMC proliferation (40)(41)(42) or may actually decrease proliferation (43,44). However, fibroblasts that are less differentiated than the other two main vascular cell types, have a greater proliferative response to hypoxia (44)(45)(46).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…Although there are reports of hypoxia driven smooth muscle cell proliferation (38,39), several in vitro studies have shown that hypoxia does not directly increase SMC proliferation (40)(41)(42) or may actually decrease proliferation (43,44). However, fibroblasts that are less differentiated than the other two main vascular cell types, have a greater proliferative response to hypoxia (44)(45)(46). Fibroblasts are uniquely positioned in the scheme of remodeling being able to rapidly proliferate, contract, migrate, synthesize cytokines and other mediators, and transdifferentiate into other cell types such as the SMC-like myofibroblast (47).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%